Towards the area and discipline of ecological (environmental) sciences - Dołęga, Józef M. (Studia Ecologiae et Bioethicae, 2003)
The presented essence of this article reveals a need of taking an area of ecological sciences or an area of environmental sciences. in other words, into account in the Polish classification of sciences. Both expressions are justified sufficiently to be accepted and taken into consideration in the Polish classification of sciences. Besides, there was a distinguished discipline: ecological sciences, or environmental sciences. An application of such the area of ecological (environmental) sciences and the discipline of ecological (environmental) sciences will enable academic schools to confer scientific degrees and scientific title in the area of ecological (environmental) sciences and within the range of determined disciplines of ecological (environmental) sciences, and a specialization: preservation of the environment. Educated specialists of this matter, of such the determined discipline and area of ecological (environmental) sciences, may have a formal basis to make researches of interdisciplinary and of system character and to create organizational units with a license to confer the scientific degrees in the discipline of ecological (environmental) sciences, and the scientifical title in the area of ecological (environmental) sciences.